Impact of nutritional supplements on kidney function in bodybuilders: a cross-sectional study - Hiba Alsharif; Asma Mesbah Elkammoshi; Najla Amer Elyounsi; Heba Milud Moftah; Intisar Miftah Abukel; Dania Rahoma; Aisha Alturki (African Journal of Advanced Pure and Applied Sciences, 2025)
The use of dietary supplements among bodybuilders has become increasingly prevalent, as individuals seek to enhance their athletic performance and achieve optimal muscle hypertrophy. Although these supplements may offer performance benefits, there is growing concern about their potential adverse effects on kidney function, particularly because the kidneys play a vital role in filtering waste products and maintaining fluid and electrolyte balance. This study aims to investigate the impact of common dietary supplements on kidney function parameters in bodybuilders. A cross-sectional analytical study was conducted involving 100 male bodybuilders aged 16 to 40 years. Participants were categorized into two groups: 50 individuals who used supplements and 50 who did not. Demographic data and supplement usage information were collected. Venous blood samples were drawn to assess kidney function markers, including serum urea, creatinine, sodium (Na), and potassium (K) levels. Data analysis was performed using SPSS version 26. Statistical significance was evaluated using independent t-tests and Pearson correlation analysis. Participants who used supplements showed significantly higher levels of urea (35.02 mg/dL vs. 29.06 mg/dL, p=0.001) and creatinine (1.08 mg/dL vs. 0.976 mg/dL, p=0.002) compared to non-users. Additionally, sodium levels were lower in supplement users (140.54 mmol/L) compared to non-users (141.65 mmol/L), with this difference being statistically significant (p=0.020). No significant difference was found in potassium levels between the two groups (p=0.584). A weak positive correlation was observed between the duration of supplement use and the levels of urea, creatinine, and potassium, while a slight negative correlation was noted with sodium. However, none of these correlations reached statistical significance. The study highlights a potential association between the use of common dietary supplements and altered kidney function markers in bodybuilders. The findings suggest that prolonged or excessive use of these supplements may contribute to renal stress or dysfunction. Therefore, it is advisable for bodybuilders and healthcare professionals to exercise caution regarding supplement use and to monitor renal function periodically.